Selective aerobic oxidation of para-xylene in sub- and supercritical water. Part 3: effects of geometry and mixing in laboratory scale continuous reactors. Issue 14 (27th January 2016) - Pérez, Eduardo; Thomas, Morgan L.; Housley, Duncan; Hamley, Paul A.; Fraga-Dubreuil, Joan; Li, Jun; Lester, Edward; Poliakoff, Martyn
Abstract : The influence of shape and mixing effects in a continuous reactor has a dramatic influence on the aerobic oxidation of p -xylene to terephthalic acid using supercritical water as solvent. Abstract : In this paper we report a strong dependence of the observed performance of the catalyst on the geometry and the configuration of laboratory scale reactors in the continuous aerobic oxidation of p -xylene in supercritical water. Small differences, such as the length of the feed pipes protruding into the reactor, have a very large effect on the observed yields and selectivities as well as on the reproducibility of the results. Different reactor designs also exert an influence on the perceived catalyst performance. We demonstrate that these effects are consistent with the relative efficiency of mixing of the reactant streams in the different reactors. The overall conclusion is that caution is required when comparing sets of data derived from studying such reactions even in apparently similar experimental arrangements.